A novel damage detection approach by using Volterra kernel functions based analysis. Issue 8 (August 2015) - Cheng, C.M.; Peng, Z.K.; Dong, X.J.; Zhang, W.M.; Meng, G.
Abstract In this paper, a novel approach is proposed to detect crack damage in nonlinear beam based on the Volterra kernel functions analysis. Volterra kernel functions are the extension of impulse response function for linear system to nonlinear system. The key issue involved in crack detection using Volterra kernel functions based analysis is the accurate identification of its kernel functions. To improve the identification accuracy of Volterra kernel functions, a wavelet balance method based approach is proposed to identify the Volterra kernel functions from observations of the in- and outgoing signals. A Volterra kernel function-based index is defined in the present study for crack detection. The new crack detection approach mainly includes three steps. First, the Volterra kernel functions are identified from the input–output data. Then, the Volterra kernel functions-based indexes are calculated. Finally, crack detection is conducted by comparing the values of the Volterra kernel functions-based indexes of the inspected beam with the values of the indexes for an uncracked beam. The numerical simulation results show that the crack detection method is sensitive to the appearance of crack in the beam, and can therefore be used as crack detection indicator to indicate the existence and the size of crack.